2022
DOI: 10.3390/app12136730
|View full text |Cite
|
Sign up to set email alerts
|

Study the Effect of eHMI Projection Distance and Contrast on People Acceptance in Blind-Spot Detection Scenario

Abstract: External human-machine interaction (eHMI) road projections are a new feature for automotive lighting to improve vehicle communication with other road users. These modalities are used to draw users’ attention and awareness to specific situations. However, such advanced capabilities are still being debated to be used on the road in the context of whether or not such road projections can provide a clear and understandable message to road users in a specific scenario or lead to anticipation and change in the drivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…In real-world scenarios, a vehicle's lights 10 meters away struggle to draw pedestrians' attention. [58] Additionally, it is crucial to ensure that pedestrians can perceive the signals the eHMI emits after drawing their attention to them. In the case of gesturebased eHMI, the recognition of actions plays a pivotal role in its effectiveness.…”
Section: Discussion 61 Specific Receiver and Clear Contentmentioning
confidence: 99%
“…In real-world scenarios, a vehicle's lights 10 meters away struggle to draw pedestrians' attention. [58] Additionally, it is crucial to ensure that pedestrians can perceive the signals the eHMI emits after drawing their attention to them. In the case of gesturebased eHMI, the recognition of actions plays a pivotal role in its effectiveness.…”
Section: Discussion 61 Specific Receiver and Clear Contentmentioning
confidence: 99%
“…We also found that VMS was effective in increasing understanding, but not behavior; however, road experiments involving VMS were not available to confirm this from this study. However, when used in combination with a road projection, a VMS may prove to be useful in increasing understanding and could potentially function as an eHMI [32,35] for other uses as well.…”
Section: Discussionmentioning
confidence: 99%
“…Road projections may provide a range of benefits including enhanced safety [17][18][19][20] and improved driving experience [18,21], among others. Road projection technology has been proposed and/or studied for a variety of applications including parking assistance [22], displaying a stop sign or other road markings [23], displaying the width of the vehicle [24,25], navigation content [26], displaying warning messages [24], and communicating driving intention or warnings [20,[27][28][29][30][31], especially in the context of connected and autonomous vehicles (CAVs) as so-called external human-machine interfaces (e-HMIs) [32][33][34][35][36][37]. On the other hand, some research investigates whether there is a possibility that these types of projections could distract drivers [23,[38][39][40].…”
Section: Introductionmentioning
confidence: 99%